Pakistan’s Water Economy : Running Dry - Briscoe, John (World Bank, Washington, DC, 2012)
With an average rainfall of under 240 milli-meters a year, Pakistan is one of the world's most arid countries. The population and the economy are heavily dependent on an annual influx of water into the Indus river system that emanates from the neighboring countries and is mostly derived from rainfall and snow-melt in the Himalayas. Throughout history, people have adapted to the low and poorly distributed rainfall by either living along river banks or carefully husbanding and managing local water resources. In the nineteenth century, the advent of large-scale irrigation technology decisively shifted the balance between man and water. In the twentieth century, Pakistan faced several political and natural challenges to its water economy. There were successfully managed through the Indus water treaty with India and the shrewd application of science, technology, and economics, but Pakistan is once again facing a number of very serious water-related threats to its survival.